Re-irradiation of head and neck cancers - Roszkowski, Krzysztof; Windorbska, Wiesława (Contemporary Oncology/Współczesna Onkologia, 2004)
Local recurrent head and neck cancers after radical treatment are undoubtedly a clinical problem. Primary radical treatment of the head and neck cancers involves a combination of surgery, chemotherapy and radiotherapy. It is often attributed with significant toxicity and intensification of the early and late reactions which permanently damage normal tissues in the treated area. When the primary tumor increases in the area of primary high dose irradiation or when the second tumor occurs in this place it is very difficult for many specialists to make the right decision about the subsequent treatment. A lot of patients with recurrent head and neck cancer who were treated with irradiation should be provided with salvage surgery. In the case of unresectable tumors or the risk of serious tissue damage re-irradiation should be considered. Re-irradiation may result in serious complications in the case of overdosage in previously irradiated area. Current literature reports complications and efficacy of this kind of management in previously irradiated head and neck cancer patients. Based on the current literature review we present outcomes and conclusions of the clinical trials that may be useful in making a clinical decision on re-irradiation.